Acetyl-l-carnitine is an anti-angiogenic agent targeting the VEGFR2 and CXCR4 pathways. (10th August 2018) - Baci, Denisa; Bruno, Antonino; Bassani, Barbara; Tramacere, Matilde; Mortara, Lorenzo; Albini, Adriana; Noonan, Douglas M.
Abstract: Carnitines play an important role in the energy exchange in cells, and are involved in the transport of fatty acids across the inner mitochondrial membrane.l -Acetylcarnitine (ALCAR) is an acetic acid ester of carnitine that has higher bioavailability and is considered a fat-burning energizer supplement. We previously found that in serum samples from prostate cancer (PCa) patients, 3 carnitine family members were significantly decreased, suggesting a potential protective role of carnitine against PCa. Several studies support beneficial effects of carnitines on cancer, no study has investigated the activities of carnitine on tumor angiogenesis. We examined whether ALCAR acts as an "angiopreventive" compound and studied the molecular mechanisms involved. We found that ALCAR was able to limit inflammatory angiogenesis by reducing stimulated endothelial cell and macrophage infiltration in vitro and in vivo . Molecularly, we show that ALCAR downregulates VEGF, VEGFR2, CXCL12, CXCR4 and FAK pathways. ALCAR blocked the activation of NF-κB and ICAM-1 and reduced the adhesion of a monocyte cell line to endothelial cells. This is the first study showing that ALCAR has anti-angiogenic and anti-inflammatory properties and might be an attractive candidate for cancer angioprevention. Highlights: ALCAR targets VEGF/VEGFR2 axis and its downstream signaling intermediates. ALCAR blocks endothelial cell migration/invasion acting on CXCR4/CXCL12 and CCL2. ALCAR downregulates inflammatory induced angiogenesis by inhibiting NF-κB and ICAM-1. ALCAR decrease endothelial cells and macrophage recruitment in vivo.